1970
DOI: 10.1017/s0021932000007574
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic and Cultural Influences on Child Growth in Rural Jamaica

Abstract: SummaryA semi-longitudinal study of growth in children up to 5 years of age in a rural Jamaican community is described. One of its aims was to investigate the relationship between growth and factors in the social environment such as family structure, parental characteristics, housing and income. A strong relationship between growth and socio-economic variables was found. This apparently masked whatever effects the quality of care or separation from parents may have had upon child growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1970
1970
1992
1992

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 4 publications
3
15
0
Order By: Relevance
“…Undernutrition, resulting mainly from infection and inadequate food intake (Chen & Scrimshaw, 1983;Mata et al, 1977), was found to be a good predictor of death (Sommer & Lowenstein, 1975;Keilmann & McCord, 1978;Chen, Chowdhury & Huffman, 1980;Trowbridge & Sommer, 1981;Briend, Wojtyniak & Rowland, 1987) and inversely correlated with socioeconomic variables (Desai, Standard & Miall, 1970;Valverde et al, 1980;Bairagi, 1982;Bhuiya et al, 1986a,b). Consequently, nutritional status has been considered as an intermediate variable through which socioeconomic factors operate to affect mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Undernutrition, resulting mainly from infection and inadequate food intake (Chen & Scrimshaw, 1983;Mata et al, 1977), was found to be a good predictor of death (Sommer & Lowenstein, 1975;Keilmann & McCord, 1978;Chen, Chowdhury & Huffman, 1980;Trowbridge & Sommer, 1981;Briend, Wojtyniak & Rowland, 1987) and inversely correlated with socioeconomic variables (Desai, Standard & Miall, 1970;Valverde et al, 1980;Bairagi, 1982;Bhuiya et al, 1986a,b). Consequently, nutritional status has been considered as an intermediate variable through which socioeconomic factors operate to affect mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The age of the target child's mother was not significantly associated with the weight for age. Desai, Standard and Miall (1970) also found no association, though others have found a positive association (Desai, Miall and Standard, 1968;Antrobus, 1971;Marchione, 1978).…”
Section: Marital Status Of Mother (Married)mentioning
confidence: 90%
“…Some studies in the West Indies have found a similar effect (Desai, Miall and Standard, 1968;Marchione, 1978), while others have found no such effect (Desai, Standard and Miall, 1970;Grantham-McGregor, Desai and Buchanan, 1977).…”
Section: Marital Status Of Mother (Married)mentioning
confidence: 90%
See 2 more Smart Citations